(untitled) (Global Media Journal - German Edition, 2020)
The article examines how nuclear risk was perceived by German and Japanese journalists covering the Fukushima Disaster. Drawing from the theoretical framework of Beck’s World Risk Society, the journalists’ personal risk perceptions are reconstructed from narrative interviews, adding an important variable to the understanding of journalistic communication on risk and disaster. The results indicate that German correspondents in Japan were highly concerned about their personal safety while Japanese journalists hardly showed any anxiety with regard to the nuclear disaster. The varying perceptions also widely applied to the journalists’ professional experience of the disaster, although further influences like organizational culture came into play as well. The article concludes that historically shaped discourses are an important macro factor for media reporting on risk and disaster.